The Central Vein: FLAIR Signal Abnormalities Associated with Developmental Venous Anomalies in Patients with Multiple Sclerosis - Rogers, D.M.; Shah, L.M.; Wiggins, R.H. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Demyelination is a recently recognized cause of FLAIR hyperintensities associated with developmental venous anomalies. Our purpose was to quantify the prevalence of white matter signal abnormalities associated with developmental venous anomalies in patients with multiple sclerosis compared with controls.MATERIALS AND METHODS: A retrospective, blinded, multireader study compared the prevalence of FLAIR hyperintense signal abnormalities adjacent to developmental venous anomalies in patients with MS compared with controls (patients with developmental venous anomalies without MS). Study findings were positive if a central vein was demonstrated using FLAIR and contrast-enhanced fat-saturated T1 sequences. Imaging parameters also included developmental venous anomaly location, developmental venous anomaly drainage, white matter lesion size, and depth of white matter lesions. Clinical parameters included age, sex, and the presence of confounding variables (hypertension, diabetes, migraines, and/or vasculopathy).RESULTS: FLAIR signal abnormality was present around 47.3% (35/74) of developmental venous anomalies in patients with MS, and 13.5% (10/74) of developmental venous anomalies in the control group (P < .001). The multivariate logistic regression model controlling for covariates (including migraines, hypertension, diabetes mellitus, vasculopathy, age, sex, and drainage direction of developmental venous anomalies) showed that the odds of FLAIR hyperintensity around developmental venous anomalies was 6.7-fold higher in patients with MS (relative risk MS = 6.68; 95% CI, 2.79–15.97; P < .001).CONCLUSIONS: The association of developmental venous anomalies and FLAIR hyperintensities was more common in patients with MS, which suggests that the underlying demyelinating pathologic process of MS may be the cause of this propensity in patients with MS. Impaired venous drainage in the territory of developmental venous anomalies may predispose to development of these lesions, and an associated central vein is helpful in understanding an atypical location of MS plaques.CCSVIchronic cerebrospinal venous insufficiencyDVAdevelopmental venous anomaly